"Estudio morfofuncional del aparato hioideo de Glyptodon cf. clavipes Owen (Cingulata: Glyptodontidae)" (Ameghiniana, 2014)
"The discovery of an exceptionally well preserved specimen of Glyptodon d. c/avipesOwen permits a morphofunctional analysis of the hyoid apparatus, The specimen was recovered from thec1iffs of the Salado River, close to General Belgrano, Buenos Aires Province, Argentina. The morphologicalmodification of the apparatus apparently occurred in response to the migration of the masticatory apparatusbelow the neurocranium that occurred in the evolution of glyptodonts. lt is characterized by thefusion of the stylo-, epi- and ceratohyoid bones of each side into a vertical rod designated here as the sigmohyoid,which is notable also for its general robustness and the great development of the areas for muscularinsertion. While other muscles are reduced, the geniohyoideus and ceratohyoideus acted antagonistically,producing powerful movernents of protraction and retraction of the tongue, respectively. The tonguewould have been more important in the reworking of food in the oral cavity than in food intake."